STUDENTS’ PERCEPTION OF DIFFICULTY LEVELS OF SENIOR SECONDARY SCHOOL CIVIC EDUCATION CURRICULUM CONTENT IN OSUN STATE, NIGERIA - William Rotimi Okunloye (IJIET (International Journal of Indonesian Education and Teaching), 2019)
The learnability of school curriculum has been attributed to students’ perception of different school subjects which also determines the level of students’ performance and ultimately the achievability of the intended curriculum objectives. Studies had been conducted in other subject area apart from Civic Education which is relatively new in the Nigerian Secondary School curriculum. This paper examines students’ perceived difficulty levels in Civic Education curriculum content and the factors associated with their perceptions. The population for the study comprised all Civic Education students in Osun State, Nigeria. Descriptive survey design was adopted for the study and a researcher- designed instrument titled Civic Education Student Syllabus Perception Questionnaire (CESPQ) was administered to 487 randomly selected students drawn from stratified randomly selected 25 Senior Secondary Schools in Osogbo, Osun state, Nigeria. The Three research questions raised for the study were answered using percentage, mean and standard deviation statistics. The results showed that the Senior School Civic Education Syllabus (SSCES) topics were perceived by students to be of different difficulty levels ranging from difficult, to very simple with an absolute majority of them being predominantly very simple. The observed difficulty levels were associated with inadequate textbooks, teachers’ presentation of lessons and wide content coverage. These imply that the Civic Education curriculum is predominantly learnable while the curriculum objectives are also predominantly achievable. Based on these findings, it was recommended that teachers should enhance the learnability of the few perceived difficult topics by students through the use of predominantly learner-centred strategies and more learner-friendly strategies to teach the subject.